Gegar Budaya dan Kecemasan: Studi Empiris pada Mahasiswa Bengkulu dan Maluku di Universitas Gunadarma dalam Beradaptasi di Lingkungan Baru - Kgs M Rio Aldino; Dinda Rakhma Fitriani (Kanal: Jurnal Ilmu Komunikasi, 2020)
The phenomenon of cultural vinegar is one of the crucial problems that often occurs among migrant communities, especially for those who migrate from the original area to the new residential area. Good consideration needs to be made to determine the success or failure of the socialization process that occurs in the new environment. The purpose of this research is to study, consider, and analyze the factors causing cultural shock and unrest in overseas students from Bengkulu and Maluku in universities that focus on Gunadarma University and how they overcome these problems. This study uses the Anxiety / Uncertainty Management Theory and intercultural adaptation theory. This study uses qualitative methods, using phenomenology and constructivist paradigms. Data collection techniques are done by interview and observation. The technique of checking validity data uses source triangulation. The results of this study show some interesting differences between overseas students from Maluku and Bengkulu that improve cultural conditions in discussion and involve social in the new environment starting from related factors (anxiety), and communication patterns used. The conclusions in this study indicate that Maluku students look more relaxed and do not consider that they really need a culture shock when they are in a new environment, while students from Bengkulu immediately point out that they really use culture shock